Comparison of weekly vs daily dosing of levothyroxine for treatment of hypothyroidism in Ramadan – a pilot randomized controlled trial: preliminary results - Zakaria, Nurul Aulia; Zakaria, Miza Hiryanti; Shahar, Mohammad Arif (2018)
INTRODUCTION : Muslim who fast during Ramadan find it difficult to take L-thyroxine as recommended every morning on empty stomach during sahur.The changes in eating patterns and gastric motility during Ramadan might affect the absorption and efficacy of L-thyroxine.This study is to compare the efficacy and safety of weekly vs daily dosing of L-thyroxine during Ramadan.